Centhini : tambangraras-amongraga - Amangkunagara III, Kanjeng Gusti Pangeran Adipati Anom, (Sunan Paku Buwana V); Penyadur, Tim; Marsono (Yogjakarta : Gadjah Mada University Press, 2010)
Prose adaptation of a classic Javanese poem.
Also issued online.
Keywords: Javanese literature -- Translations into Indonesian; Indonesian literature -- Translations from Javanese; Javanese literature -- History and criticism